Hydrocarbons in Deep-Sea Sediments following the 2010 Deepwater Horizon Blowout in the Northeast Gulf of Mexico - Romero, Isabel C. (PLoS One, 2015)
The Deepwater Horizon (DWH) spill released 4.9 million barrels of oil into the Gulf of Mexico (GoM) over 87 days. Sediment and water sampling efforts were concentrated SW of the DWH and in coastal areas. Here we present geochemistry data from sediment cores collected in the aftermath of the DWH event from 1000 – 1500 m water depth in the DeSoto Canyon, NE of the DWH wellhead. Cores were analyzed at high-resolution (at 2 mm and 5 mm intervals) in order to evaluate the concentration, composition and input of hydrocarbons to the seafloor. Specifically, we analyzed total organic carbon (TOC), aliphatic, polycyclic aromatic hydrocarbon (PAHs), and biomarker (hopanes, steranes, diasteranes) compounds to elucidate possible sources and transport pathways for deposition of hydrocarbons. Results showed higher hydrocarbon concentrations during 2010-2011 compared to years prior to 2010. Hydrocarbon inputs in 2010-2011 were composed of a mixture of sources including terrestrial, planktonic, and weathered oil. Our results suggest that after the DWH event, both soluble and highly insoluble hydrocarbons were deposited at enhanced rates in the deep-sea. We proposed two distinct transport pathways of hydrocarbon deposition: 1) sinking of oil-particle aggregates (hydrocarbon-contaminated marine snow and/or suspended particulate material), and 2) advective transport and direct contact of the deep plume with the continental slope surface sediments between 1000-1200 m. Our findings underline the complexity of the depositional event observed in the aftermath of the DWH event in terms of multiple sources, variable concentrations, and spatial (depth-related) variability in the DeSoto Canyon, NE of the DWH wellhead.